Pathways to citizenship through naturalisation in Ireland - Sarah Groarke; Róisín Dunbar (The Economic and Social Research Institute (ESRI), 2020)
New ESRI/European Migration Network research finds that Ireland has more favourable conditions for acquiring citizenship by naturalisation than many EU Member States. However, processing delays and lack of clarity on some eligibility conditions have been highlighted by NGOs and in parliamentary debate. There are three main "pathways" to Irish citizenship: at birth by descent, by birth on the island of Ireland, and naturalisation. This study is part of EU-wide research on naturalisation, which is the main way by which migrants may access citizenship and its associated rights.
Keywords: 330; Staatsangehörigkeit; Migrationspolitik; Irland